Hubungan Pemahaman Risiko Penyakit dengan Konsistensi Pemberian Imunisasi Dasar Pada Balita - Sigit Aji Putranto; Nopi Nur Khasanah; Kurnia Wijayanti (Journal of Health, Medical, and Psychological Studies, 2025)
Basic immunization is a public health intervention that effectively reduces morbidity and mortality caused by vaccine-preventable infectious diseases. Problems related to the consistency of immunization schedules are still encountered, including in Semarang City. One factor that is believed to play a role is the level of parents’ understanding of the risks of diseases that can be prevented through immunization. This study aimed to analyze the relationship between parents’ understanding of disease risk and the consistency of basic immunization among toddlers at Bangetayu Public Health Center. The study used a quantitative approach with a descriptive correlational design. A total of 101 parents of children aged 9–59 months were selected through purposive sampling. Data were collected using structured questionnaires and observation of the Maternal and Child Health (MCH) handbook. Data analysis was conducted descriptively and using the Chi-Square test with α = 0.05. The results showed that 46.5% of respondents had a moderate level of understanding of disease risk and 58.4% provided basic immunization consistently. The Chi-Square test indicated a significant relationship between parents’ understanding of disease risk and the consistency of basic immunization among toddlers (p = 0.001). This indicates that the better the parents’ understanding, the higher the consistency of basic immunization among toddlers.